Does biodiversity matters in the tourism demand model? International evidence - Jaz, Nur Ameera; Habibullah, Muzafar Shah; Azman-Saini, WNW; Kaliappan, Shivee Ranjanee (Portuguese Association for Regional Development, 2023)
This study examines the role of natural attractions, measured by biodiversity, in drawing international tourists. This study examines a global sample of 120 countries from 2010 to 2016. Several static approaches such as Pooled Ordinary Least Square (POLS), Random Effect (RE) and Fixed Effect (FE) models were used to estimate the static effect between biodiversity and international tourist arrivals. The robust standard error results show that the choice of a tourism destination is strongly related to biodiversity. The results also indicate that GDP per capita, good governance, investment in the travel and tourism sector, and the internet are positively significant in determining tourism demand.